The magmatic evolution of the Neotethyan rift: Geochronologic, isotopic, and geochemical evidence from A-type felsic magmatism, NW Iran. (May 2021) - Nabatian, Ghasem; Li, Xian-Hua; Honarmand, Maryam; Esmaeili, Rasoul
Highlights: Ajabshir A-type rhyolite magma formed during the Early Carboniferous. The Ajabshir rhyolite magma formed through rifting of the Neotethyan Ocean. A mixed source of enriched mantle and juvenile crust is suggested for rhyolite magma. Different magmatic features happened in branches of Neotethyan triple junction. Abstract: The Ajabshir rhyolitic magma in the northwest (NW) of Iran is an Early Carboniferous (332.5 ± 2.2 Ma), approximately 50m-thick succession, consisting of quartz, alkali feldspar, and biotite phenocryst with a porphyritic texture. This magmatic unit occurred as lava flows and sills intruded into the early Cambrian Lalun Formation. The Ajabshir magma has a calc-alkaline to high potassic calc-alkaline affinity and peraluminous character and displays many of the classic features of A-type magmas, enrichment in HFSEs (Zr + Nb + Ce + Y = 664–808 ppm), Nb (120−218 ppm), Zr (298−362 ppm), Ga (34−38 ppm), Ce (100−132 ppm), high Ga/Al and FeO*/(FeO*+MgO), zircon saturation temperature, and low contents of CaO, Sr, and Eu. The LREE enrichment, non-depletion in HREE, and negative Eu anomalies in the chondrite normalized diagrams exhibit similarities to the REE patterns of "hot-dry-reduced rhyolites", further pointing to the evolution of Ajabshir rhyolitic magma from an OIB-type parental melt via a fractional crystallization process. The zircon yield εHf(t) values of +1.4 to +5.5 correspond to two-stage zircon Hf model ages of 0.9–1.2 Ga. The δ 18 O values of the zircon range from +5.8‰ to +7.37‰. The zircon isotopic data together with whole-rock geochemical signatures suggest that the mantle-derived magma was modified by crustal components during its ascent to the surface. The Ajabshir A-type rhyolitic magma provides more evidence for an extensional tectonic setting during the Early Carboniferous in NW Iran, contemporaneous with the rifting of the Neotethyan Ocean at the northern margin of Gondwana.